New Finds Offering Insights into the Knight’s Manor in Chechło, Upper Silesia - Radosław Zdaniewicz (Acta Universitatis Lodziensis: Folia Archaeologica, 2022)
The archaeological research conducted in 1970 confirmed that there are remains of a late medieval motte-and-bailey castle in Chechło. At that time, the structure was almost completely destroyed by farmstead construction, with only one small section of an earth wall preserved. During the conservator’s intervention in 1998, hundreds of unprocessed artefacts were discovered in the collection of the Provincial Office of Monument Preservation in Katowice, again drawing attention to this interesting site. Due to the expansion of the farmstead, the cultural stratification of the motte-and-bailey castle was damaged. Today, degradation and destruction by the contemporary infrastructure make it impossible to conduct further verification research, which would allow to better explore the remains of the site. Based on written sources and analysis of the finds, we can draw some new conclusions concerning its operation. There is no doubt that the manor already existed in the fourteenth century and that it was also used in the following centuries. It is difficult to say anything about the appearance of the manor at the time. It was most probably surrounded by an earth wall, small remains of which have been preserved until today. The discovered ceramic shards and fragments of stove tiles indicate that the residence was still used in the modern era, meaning the sixteenth and seventeenth centuries, by representatives of the local gentry.